The influence of social capital on farmers’ green control technology adoption behavior - Ren, Zhong; Fu, Zitian; Zhong, Kaiyang (Frontiers in Psychology, 2022)
Relying on social capital to promote farmers' adoption of green control technology is of great significance for the governance of rural environment and the realization of sustainable agricultural development. Based on the survey data of 754 farmers in Shandong Province, this paper uses the Probit model and the instrumental variable method to empirically analyze the impact of social capital on farmers' green control technology adoption behavior. The results show that: social capital has a promoting influence on farmers' green control technology adoption behavior; the influence of the three dimensions of social capital on farmers' green control technology adoption behavior is in turn social norms, social networks, and social trust; social networks play an enhanced moderating role in the process of social trust and social norms promoting farmers' green control technology adoption behavior; education level, the number of family labor force and annual family income level have a significant positive impact on farmers' green control technology adoption behavior, while age has a significant negative impact. Therefore, the government should make full use of social capital to promote farmers to adopt green control technology.